A packet priority intimation-based data transmission for congestion free traffic management in wireless sensor networks. (November 2017) - Shelke, Maya Padmakar; Malhotra, Akshay; Mahalle, Parikshit
Highlights: A congestion prevention mechanism is proposed. This mechanism is based on priority of information included in packet being transmitted. It introduces packet priority intimation bit in each packet to reflect its priority. It ensures transmission of high priority packets with minimum delay as it reduces priority comparison time of different packets. It also improves throughput and packet delivery ratio in wireless sensor network. Abstract: Congestion in Wireless Sensor Networks (WSN) reduces network performance by lowering throughput and increasing delay in transmitting packets. Many WSN applications rely on timely transmission of information to the destination. In such networks congestion control mechanisms play an important role to protract network lifetime, improve fairness and Quality of Service(QOS) in terms of throughput, packet delivery ratio and end-to-end delay. This paper proposes packet priority intimation-based (PPI) congestion control mechanism. We introduce a PPI bit in each packet to reflect its importance. Main objective of this mechanism is to send higher priority packets with minimum delay. The proposed PPI mechanism is deployed in the existing AODV routing protocol to convert the existing routing protocol to a congestion aware routing protocol. The performance of the proposed approach is simulated in Network Simulator (NS2) software and the efficiency is verified. The simulation results are compared with that of an existing approach. Graphical abstract: